Rectifier controlled by fuzzy logic controller - Abd. Halim, Fakhrul Razi (2008)
This paper presents a fuzzy logic controller for rectifier output voltage. A rectifier is a circuit that converts ac signal to dc signal. The used of fuzzy logic controller is based on the error of the output voltage and the differences between new error and present error. Fuzzy logic controller will improve the simulation performances. The sinusoidal phase with modulation (SPWM) was used as the switching pattern for the rectifier circuit. The modeling and simulation model of the rectifier is using MATLAB/Simulink with the Sim Power System Block set. Performances of the rectifier are compared between one input of fuzzy logic and two inputs.